IMPLEMENTASI PROGRAM INDONESIA PINTAR PADA TINGKAT SEKOLAH DASAR DI KOTA PEKANBARU - Ewina Ratu; Hasim As’ari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The Smart Indonesia Program (PIP) is a cash assistance provided by the government to students from underprivileged families who have difficulty paying tuition fees. This program was created to reduce the dropout rate for children caused by economic factors. This study aims to determine the implementation of the Smart Indonesia Program at the elementary school level and identify the inhibiting factors in the implementation of the Smart Indonesia Program at the elementary school level in Pekanbaru city. This study uses a descriptive qualitative method and the required data, both primary and secondary data, were obtained through observation, interviews and documentation. This study uses the theory of David C. Korten which has indicators of program with beneficiaries, programs with implementing organizations, and groups of beneficiaries with implementing organizations. The results showed that the implementation of the Smart Indonesia Program in the city of Pekanbaru was not effective and efficient because there were still several indicators that had not been fulfilled and several phenomena were found in the field regarding the implementation of this program. Although, there were still participants who complained that there were deficiencies and that they were not fully optimal because there were several things that needed to be considered for evaluation. The inhibiting factors are information, limited organizational capacity, and the use of funds.Keywords: Implementation, Smart Indonesia Program, Organizations, Beneficiaries.